2019
DOI: 10.1002/biof.1574
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a role of the novel hepatokine, hepassocin, in obesity

Abstract: Obesity is a public health problem that has raised concerns worldwide and is often associated with hepatic steatosis. Hepassocin is a novel hepatokine that causes hepatic steatosis and induces insulin resistance (IR). However, the role of hepassocin in obesity remains obscure. Thus, the aim of this study was to investigate the relationship between hepassocin levels and obesity. In total, 371 subjects who had a normal weight (NW), were overweight, or were obese were enrolled. We found that hepassocin levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Recently, the relationship between FGL1 and obesity was confirmed in obese individuals. The plasma FGL1 of obese subjects was higher than that of healthy individuals, and univariate analysis confirmed that BMI, waist circumference, total fat, visceral fat, and subcutaneous fat area were all positively correlated with FGL1 level [31]. FGL1 null mice were shown to have abnormal plasma lipid profiles, fasting hyperglycemia and exhibited differences in white and brown adipose tissue morphology [5].…”
Section: Fgl1 In Obesitymentioning
confidence: 83%
“…Recently, the relationship between FGL1 and obesity was confirmed in obese individuals. The plasma FGL1 of obese subjects was higher than that of healthy individuals, and univariate analysis confirmed that BMI, waist circumference, total fat, visceral fat, and subcutaneous fat area were all positively correlated with FGL1 level [31]. FGL1 null mice were shown to have abnormal plasma lipid profiles, fasting hyperglycemia and exhibited differences in white and brown adipose tissue morphology [5].…”
Section: Fgl1 In Obesitymentioning
confidence: 83%
“…Obesity is closely associated with insulin resistance and NAFLD. Hepassocin levels were significantly upregulated in overweight and obese subjects [ 215 ]. Moreover, serum hepassocin was positively correlated with obesity indices, including body mass index, waist circumference, and fat areas (total, visceral, and subcutaneous) in humans [ 75 ].…”
Section: Hepatokines and Nafldmentioning
confidence: 99%
“…Moreover, hepatokine secretion is generally improved after bariatric surgery, which might drive the long-term metabolic improvements following bariatric surgery [24]. Recently, studies found that plasma FGL-1 levels are associated with obesity [25]. However, the role of FGL-1 in patients with obesity who undergo LSG remains obscure, and purpose of the present study is to investigate the changes of FGL-1 after LSG, and whether it is correlated with other metabolic indices.…”
Section: Discussionmentioning
confidence: 96%